Why Indonesia Maintain Capital Punishment? - Ahmad Irzal Fardiansyah (Fiat Justisia: Jurnal Ilmu Hukum, 2021)
The death penalty in Indonesia is still maintained to combat crime within the Indonesian criminal law reform. Although many states have it removed, Indonesia would have the sole discretion to keep it. Despite the opposition, the death penalty application still has a juridical and sociological basis, so it is still legal to be maintained. Indonesia itself has overshadowed the death penalty with a form of legality according to international law so that the position of Indonesia that still maintain the death penalty cannot be blamed. Moreover, sociologically, Indonesian people still accept those who commit an offence who may have profound implications that could lead to the death penalty. This issue is what became the basis for lawmakers in Indonesia to keep it. This research uses the doctrinal method toexamine various regulations regarding capital punishment and non-doctrinal to understand the community's situation related to the existence of capital punishment in Indonesia. The death penalty is a more effective deterrent and therefore prevents crime better. With the death penalty, others were about to commit a similar crime is expected not to commit the crime. The death penalty is more effectively immobilizing offenders. Perpetrators, in principle, still manage to have the desire to commit the crime again after release. The death penalty for perpetrators of crimes is not a violation of human rights, but rather to respect human rights itself, namely for victims of crime. The setting and the application of the death penalty in Indonesia until now is still needed. They are considering that there are still many crimes that undermine humanity's values or the crimes that harm the State and crackdown on corruption in society.